The stereoselective conversion of epimerized alkoxyl phosphine–borane to P, C, axial-stereogenic tertiary phosphine via cleavage of P–O bond. Issue 13 (17th March 2022) - Zhai, De-Hua; Yan, Bing-Xia; Li, Zhan-Cai; Lin, Zhu; Li, Qiang; Wang, Yan-Lan; Zheng, Hong-Xing; Zhao, Chang-Qiu
Abstract : The epimerized alkoxyl phosphine–borane was converted to P-anions in 86 : 14 dr, and further to tertiary phosphine in 96 : 4 dr when alkylated, and was used for preparation of multi-stereogenic tertiary phosphines. Abstract : The P–O bond of epimerized alkoxyl phosphine–borane was cleaved by naphthalene-lithium, to form two diastereomers of P-anions in a ratio of 86 : 14, which was then converted to secondary phosphine–borane via acidification, and to tertiary phosphines with alkyl halides with enhanced 96 : 4 dr. The isolated tertiary phosphine containing hydroxyl (in >99 : 1 dr) was converted to multi-stereogenic tertiary phosphines via O -alkylation with alkylene dihalides.